Preparation and Structural Characterization for Polyacrylonitrile/Carbon Nanotubes Composites Treated with Concentrated Nitric Acid - Ji, Bao-Hua (Asian Journal of Chemistry, 2012)
The multi-walled carbon nanotubes were modified by conc. HNO3, the composite of multi-walled carbon nanotube and poly(acrylonitrile) (PAN) was manufactured by aqueous deposited polymerization method. The effect of multi-walled carbon nanotube on the thermal and crystallization properties of poly(acrylonitrile) composites was discussed. It is demonstrated that the preoxidation temperature of PAN/CNTs composites is in advance to a certain extent than those of pure poly(acrylonitrile) polymers, its heat release reduces obviously and the crystallization degree for polymers decreases a little but not changing the basic structure of polymer films. Consequently, the homogeneously-dispersed PAN/CNTs composites are achieved and the compatibility between the polymer and carbon nanotubes is improved remarkably.